2004
DOI: 10.1145/966389.966391
|View full text |Cite
|
Sign up to set email alerts
|

Puzzles in software development contracting

Abstract: Current outsourcing practices are relatively unsophisticated in comparison with the techniques prescribed by economic theory. Customers end up bearing all long-term risk, and vendors have no direct incentive to achieve long-term system effectiveness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 9 publications
0
29
0
2
Order By: Relevance
“…In contrast, project size attributes, such as price and duration, are easily observed. Managers thus frequently base their contract choices solely on project size attributes (Lichtenstein, 2004). The reasoning and findings of our contracting-cost mediation model suggest that managers should pay more attention to project detail and vendor familiarity in making contract choices.…”
Section: Implications and Limitationsmentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, project size attributes, such as price and duration, are easily observed. Managers thus frequently base their contract choices solely on project size attributes (Lichtenstein, 2004). The reasoning and findings of our contracting-cost mediation model suggest that managers should pay more attention to project detail and vendor familiarity in making contract choices.…”
Section: Implications and Limitationsmentioning
confidence: 89%
“…Research on software development outsourcing similarly distinguishes between FP contracts, in which the price for delivery is prespecified, and T&M contracts, in which the vendor is reimbursed for its costs plus a predetermined profit (Banerjee & Duflo, 2000;Gopal et al, 2003;Lichtenstein, 2004;Whang, 1992).…”
Section: Contract Choice In Software Development Outsourcingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang & Beath, 1993;Banerjee & Duflo, 2000;Banker & Kemerer, 1992;Richmond & Seidelmann, 1993;Richmond, Seidmann, & Whinston, 1992;Wang, Baron, & Seidmann, 1997;Whang, 1992) describe features of contracts, contract types and pricing structures and investigate their economical role, but do not relate them to actual systems development practice. Lichtenstein and McDonnell (2003) and Lichtenstein (2004) are an exception. Considering software development as outsourcing and based on an economical perspective they formulate a number of hypotheses about the relationship between frequency of milestones, project risk, uncertainty and price structure as determined in systems development contracts, but they do not obtain any clear results.…”
Section: Introductionmentioning
confidence: 98%
“…According to Kerzner [5], research and analyses of projects completed based on outsourcing should consider the relations between the client and the supplier. We need to indicate, following Lichtenstein [6], that there is a partial incompatibility of interest between the client and the supplier, manifesting itself in a clear contradiction between the maximization of the supplier's profit and the client's wish to complete the project at the lowest possible cost. My research [2] has confirmed Lichtenstein's observations-the goals and interests of a client and a supplier implementing an IT project are partially contradictory.…”
mentioning
confidence: 99%